Necessity of early correction of anal-coccygeal ligaments in traumatic damage to a coccyx (Perioperaciina Medicina, 2019)
In order to prevent and correct the defecation disorders after destruction of the anococcygeal ligament, the meth-od of restoring its functional capacity was proposed (Patent of Ukraine for Invention No. 115280 “Method for Coccyx Re-moving”).It is proved that the damaging effect in the area of the traction and contraction mechanism of action on the rectum in 90.0% leads to continence disorders due to changes in the size of the anorectal angle due to the persistent disorders of the anococcygeal ligament function. The developed special mathematical model of the anococcygeal ligament function testifies that, when it is destroyed, the change in the anorectal angle value may reach changes in its value up to ≈63°, which distorts the direction of the anal canal and the distal rectum. Restoration by simulating of the anatomical fixation of anococcygeal ligament connection after its damage creates conditions for resto-ration of its physiological functioning.
Keywords: children; chronic colostasis; diagnostics; treatment; anococcygeal ligament